Agricultural innovation in Costa Rica and its effects on the development of rural territories: the challenges of a complementary agenda - Barboza Arias, Luis M. (2020)
This paper aims to identify the evolution of the Costa Rican agricultural innovation system (AIS), by characterizing both systemic actors and functions. The paper also studies the interactions between rural territorial development and agricultural innovation. The principal research questions are: how does the Costa Rican agricultural innovation system evolve? And what is the role of organizations involved in innovation processes? A quantitative methodology is used in this study. Conclusions show that the Costa Rican AIS is evolving towards an interactive learning scheme in which local actors are becoming increasingly recognized by institutional actors. However, the effects of this relationship on territorial development are poorly addressed.